Inequalities in glycemic and multifactorial cardiovascular control of type 2 diabetes: The Heart Healthy Hoods study - Ares-Blanco, Sara; Polentinos-Castro, Elena; Rodríguez-Cabrera, Francisco; Gullón, Pedro; Franco, Manuel; del Cura-González, Isabel (Frontiers in Medicine, 2022)
Aim: To analyse glycemic control and multifactorial cardiovascular control targets in people with type 2 diabetes (T2DM) in primary care according sex and socioeconomic status (SES). Methods: Observational, cross-sectional, multicenter study. We analyzed all the T2DMM patients between 40-75 years in Madrid city (113,265) through the electronic health records from 08/01/2017 to 07/31/2018. SES was defined by area-level socioeconomic index stratified by quintiles (1st quintile: more affluent). Outcomes: glycemic control (HbA1c≤ 7%) , 3-factor cardiovascular control (HbA1c ≤ 7%, blood pressure (BP), < 140/90 mm Hg, LDL <100 mg/ml) and 4-factor control (HbA1c ≤ 7%, blood pressure (BP), < 140/90 mm Hg, LDL <100 mg/ml and BMI<30 kg/m2). Multilevel logistic regression models analyzed factors associated with suboptimal glycemic control. Results: 43,2% were female. Glycemic control was achieved by 63% of patients (women: 64.2% vs men: 62.4%). Being more deprived was associated with suboptimal glycemic control (OR: 1.20, 95% CI: 1.10-1.32), however, sex was not related (OR:0.97, 95%CI: 0.94-1.01). The optimal 3-factor control target was reached by 10.3% of patients (women: 9.3% vs men: 11.2%), especially those in 5th quintile of SES. The 4-factor control was achieved by 6,6% of the sample. In 3-factor control target, being female was related to suboptimal 3-factor control target (OR:1.26, 95% CI: 1.19-1.34) but only belonging to SES 4th quintile was related to unachieved target (OR: 1.47, 95% CI:1.04-2.07). Conclusions: Suboptimal glycemic control was associated with being less affluent and suboptimal 3-factor control target was associated with being female.